Two linguistic postulates of quechua: certainty and warmth - Meneses Tutaya, Norma (2019)
In this study, two linguistic postulates of Quechua Chanka are presented. These postulates show some cognitive principles and values of the Andean culture. From the concept of postulate established by Hardman (1972), it is proposed that a linguistic postulate to be considered as such must configure a small morphological system relatively stable. The basic meaning of this system has to be directly related to the cognitive principles and values or norms of behavior of a culture. I have named the two identified postulates as the postulate of certainty and the postulate of warmth due to the basic meaning that their respective morphemes share internally. The postulate of certainty is formed by the independent or discursive suffixes: -mi, -si, -cha, -puni, and their forms combined with the morphemes -iki and -á. The linguistic postulate of warmth has a complex manifestation since it consists of both nominal and verbal derivative suffixes as well as independent suffixes: -cha, -cha, -ri, -yku, -taq, -lla, -y, -á, -ri and its combined forms.